Dual-modality Chemo-photodynamic Therapy Using RB and DOX as Anti-cancer Drugs by PAMAM-grafted Hollow Porous Silica Nanoparticles - Zhou, Junshuai; Yang, Yunjie; Zheng, Yan-Zhen; Tao, Xia (Current Nanoscience, 2017)
Background: Photodynamic therapy (PDT) which has been approved by FDA is a noninvasive clinical method for the treatment of various cancer and non-cancer diseases. In this work, we herein develop a dual-modality chemo-photodynamic therapy in the G3-PHSNPs drug delivery system, in which rose bengal (RB), an anionic water soluble xanthene dye capable of photocatalytic conversion of oxygen molecule to 1O2 upon irradiation, was used as a photodynamic sensitizer and then anchored to G3-PHSNPs via electrostatic interaction, and subsequently doxorubicin (DOX) as a chemo-therapeutic agent was also loaded onto the same silica cargo via a simple immersion process. Methods: The experiment includes loading of RB onto G3-PHSNPs, chemical method-based detection of 1O2, cell culture and assessment of particle endocytosis, loading and release of DOX onto RBG3- PHSNPs, and cell phototoxicity assay. Results: In vitro studies have demonstrated the active uptake of the RB loaded G3-PHSNPs into the cytosol of tumor cells. Irradiation of the RB-entrapped G3-PHSNPs with light results in efficient generation of highly active 1O2 species. A considerable high loading efficacy and sustained release of DOX may be obtained on account of the inherent structural features of the self-made silica material. In vitro cytotoxicity assays showed that DOX-RB-PHSNPs photoinduced higher cell death compared to the combination of free DOX and RB. These results demonstrate that functionalized therapeutic complexes are potential dual carriers for the combination of photodynamic therapy and chemotherapy in future treatment of cancer. Conclusion: G3-PHSNPs have been successfully fabricated as drug vehicles for dual-modality chemo-photodynamic therapy by assembling RB to amino groups of PAMAM dendrimers located at the external region of silica carriers and subsequently loading DOX in the inner voids/wall pore channels of silica material. The final cell viability of DOX-RB-G3-PHSNPs is lower than that of the combination of free DOX and RB, and the dual-modality DOX-RB-G3-PHSNPs drug-carrier vehicles boosts the combined cell-killing efficacy of DOX and RB.
Keywords: rose bengal